The most frequent nursing diagnosis in pediatric intensive care unit - Danila Maria Batista Guedes; Lisabelle Mariano Rossato; Eloíde André Oliveira (Universidade Federal de Santa Maria, 2015)
Aim: to identify the ten most frequent nursing diagnosis in hospitalized patients in a Pediatric Intensive Care Unit. Method: cross-sectional study with 30 patients in a Pediatric Intensive Care Unit. The data were collected during the January and February 2013. Results: the nursing diagnosis, according to the taxonomy of North American Nursing Diagnosis Association: Risk of infection (86,67%), Dysfunctional gastrointestinal motility (60%), Ineffective airway clearance (53,3%), Risk of impaired skin integrity (40%), Risk of vascular trauma (40%), Risk of electrolyte imbalance (36,67%), Impaired spontaneous ventilation (36,67%), Acute pain (33,3%), Constipation (33,3%), Impaired skin integrity (26,67%). Conclusions: the identification of the nursing diagnosis can contribute to implementation of the Nursing Care Systematization at the Pediatric Intensive Care Unit, allowing that assistance to be targeted and specified to actual and potential health problems of the subject to be cared